“Nachfolge” by Bonhoeffer: The „Imitatio Christi” of the 20ᵗʰ Century - ȘUTEU, Fănel (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Eight decades are precisely marked since Nachfolge,the work of the Lutheran pastor and theologianDietrich Bonhoeffer (1906–1945), has appearedin the German realm (1937). In 2009, 72years since that date, the Cluj publisher Peregrinul,published this book in Romanian language.There lies a possibility of the title being translatedliterally but hermetically, such as: „Succession”,„Emulation”, or „Imitation”. The latter refers to awriting by a medieval monk called Hammerkin,Die Nachfolge Christi (it is about the extremelywell known work by Thomas a Kempis, ImitatioChristi). Ligia Taloș – the translator of Bonhoeffer’swork – chose a title accessible to the commonChristian reader, probably drawing inspiration fromthe English version The Cost of Discipleship.